COUNSELING ON LEARNING ENGLISH WITH THEME OF STRENGTHENING PANCASILA PROFILE TO STUDENTS AT KINDERGARTEN OF AN NUUR, MOJOROTO DISTRICT, KEDIRI CITY - Yoyok Febrijanto; Nofa Novera (Kirana Publisher, 2023)
This community service activity aims to improve the teaching skills of kindergarten teachers at Kindergarten of An Nuur, Mojoroto District, Kediri City in terms of learning methods, namely the play pictures method, the story method, and the demonstration method. While the type of counseling that was carried out was an effective way of learning for kindergarten students. The results of this community service activity was that the understanding and ability of kindergarten teachers regarding effective learning methods for kindergarten students can be improved by conducting counseling; teacher's understanding and ability can increase success in learning the subject matter. In addition, understanding parents of kindergarten students about how their children learn and understanding. By understanding the parents of kindergarten students, they have improved how their children learn, understand every subject explained by kindergarten teachers, and not forcing their children to complete homework properly.